A Novel Bone Substitute with High Bioactivity, Strength, and Porosity for Repairing Large and Load‐Bearing Bone Defects. Issue 8 (18th February 2019) - Li, Jiao Jiao; Dunstan, Colin R.; Entezari, Ali; Li, Qing; Steck, Roland; Saifzadeh, Siamak; Sadeghpour, Ameneh; Field, John R.; Akey, Austin; Vielreicher, Martin; Friedrich, Oliver; Roohani‐Esfahani, Seyed‐Iman; et al.
Abstract: Achieving adequate healing in large or load‐bearing bone defects is highly challenging even with surgical intervention. The clinical standard of repairing bone defects using autografts or allografts has many drawbacks. A bioactive ceramic scaffold, strontium‐hardystonite‐gahnite or "Sr‐HT‐Gahnite" (a multi‐component, calcium silicate‐based ceramic) is developed, which when 3D‐printed combines high strength with outstanding bone regeneration ability. In this study, the performance of purely synthetic, 3D‐printed Sr‐HT‐Gahnite scaffolds is assessed in repairing large and load‐bearing bone defects. The scaffolds are implanted into critical‐sized segmental defects in sheep tibia for 3 and 12 months, with bone autografts used for comparison. The scaffolds induce substantial bone formation and defect bridging after 12 months, as indicated by X‐ray, micro‐computed tomography, and histological and biomechanical analyses. Detailed analysis of the bone‐scaffold interface using focused ion beam scanning electron microscopy and multiphoton microscopy shows scaffold degradation and maturation of the newly formed bone. In silico modeling of strain energy distribution in the scaffolds reveal the importance of surgical fixation and mechanical loading on long‐term bone regeneration. The clinical application of 3D‐printed Sr‐HT‐Gahnite scaffolds as a synthetic bone substitute can potentially improve the repair of challenging bone defects and overcome the limitations of bone graft transplantation. Abstract : Strontium–hardystonite–gahnite scaffolds show strong ability to repair large and load‐bearing defects in the long bones of sheep over 1 year, without the addition of cells or growth factors. These 3D printed bioactive ceramic implants may be useful as purely synthetic bone substitutes to augment the clinical treatment of challenging bone defects.